Developmental changes in face visual scanning in autism spectrum disorder as assessed by data-based analysis - Amestoy, Anouck; Guillaud, Etienne; Bouvard, Manuel P.; Cazalets, Jean-René (Frontiers in Psychology, 2015)
Individuals with Autism Spectrum Disorder (ASD) present reduced visual attention to faces. However, contradictory conclusions have been drawn about the strategies involved in visual face scanning due to the various methodologies implemented in the study of facial screening. Here, we used a data-driven approach to compare children and adults with ASD subjected to the same free viewing task and to address developmental aspects of face scanning, including its temporal patterning, in healthy children and adults. Four groups (54 subjects) were included in the study: typical adults, typically developing children, and adults and children with ASD. Eye tracking was performed on subjects viewing unfamiliar faces. Fixations were analyzed using a data-driven approach that employed spatial statistics to provide an objective, unbiased definition of the areas of interest. Typical adults expressed a spatial and temporal strategy for visual scanning that differed from the three other groups, involving a sequential fixation of the right eye, left eye and mouth. Typically developing children, adults and children with autism exhibited similar fixation patterns and they always started by looking at the right eye. Children (typical or with ASD) subsequently looked at the left eye or the mouth. Based on the present results, the patterns of fixation for static faces that mature from childhood to adulthood in typical subjects are not found in adults with ASD. The atypical patterns found after developmental progression and experience in ASD groups appear to remain blocked in an immature state that cannot be differentiated from typical developmental child patterns of fixation.